2018
DOI: 10.1186/s12913-018-3097-7
|View full text |Cite
|
Sign up to set email alerts
|

Responsibilities with conflicting priorities: a qualitative study of ACT providers’ experiences with community treatment orders

Abstract: BackgroundPatients with severe mental illness may be subjected to Community Treatment Orders (CTOs) in order to secure that the patients adhere to treatment. Few studies have investigated the use of CTOs within an Assertive Community Treatment (ACT) setting, and little is known about how the tension between the patients’ autonomy and the clinicians’ responsibility to act in the patients’ best interest are resolved in practice. The aim of this study was to explore the service providers’ experiences with CTOs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The papers reviewed spoke about communication and emphasized approach as a way to promote PCC. Communication which was person centred was viewed as direct or clear (Dawson, Lawn, Simpson, & Muir-Cochrane, 2016;Stuen, Landheim, Rugkasa, & Wynn, 2018), empathic (Courtney & Moulding, 2014) and consistent (Barnao, Ward, & Casey, 2015). Another way communication was used as a form of PCC was by asking for service user feedback and input in treatment plans or assessments (Dawson et al, 2016;Proctor, 2005;Stuen et al, 2018).…”
Section: Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The papers reviewed spoke about communication and emphasized approach as a way to promote PCC. Communication which was person centred was viewed as direct or clear (Dawson, Lawn, Simpson, & Muir-Cochrane, 2016;Stuen, Landheim, Rugkasa, & Wynn, 2018), empathic (Courtney & Moulding, 2014) and consistent (Barnao, Ward, & Casey, 2015). Another way communication was used as a form of PCC was by asking for service user feedback and input in treatment plans or assessments (Dawson et al, 2016;Proctor, 2005;Stuen et al, 2018).…”
Section: Communicationmentioning
confidence: 99%
“…Although service users found coercive care to be prescriptive and rigid, some also acknowledged that there were times where such control was necessary (Seed et al, 2016). This was similar for compulsory community treatments, as some service providers felt such mechanisms were necessary to support overall goals for recovery (Stuen et al, 2018). Geller (2012), suggests that directly acknowledging and addressing the imbalance of power in coercive care environments between providers and users is one way to increase perceived choice.…”
Section: Choice and Controlmentioning
confidence: 99%
“…Our data show that the ACT providers perceived that the multidisciplinary nature of their work allowed for frequent patient contact, coordinated support, relationship building and more flexible treatment options. As a specific component of clinical care, the ACT model’s focus on everyday activities and improving patients’ lives was seen as pivotal to improve patients’ well-being and to gradually help patients work toward greater independence and self-sufficiency [ 30 ]. Further, the ACT team’s long-term treatment perspective and the ways in which the teams often managed to gradually involve patients in treatment decisions and joint crisis planning were considered as important in reducing the use of coercion [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ACT model has a strong focus on promoting patients’ autonomy and recovery [ 28 , 29 ], and, as we have shown previously, the enactment of CTOs typically involves competing priorities and role tensions [ 30 ]. Some studies show that assertive outreach teams reported using less intrusive approaches than other community mental health services [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 A study that interviewed health professionals highlighted the dilemma of combining the role of the therapist with a control function, even if they saw that OC provided a secure framework for treatment. 10 Another study of relatives of patients with OC decisions referred to the positive experience of OC providing safety and ensuring functioning in daily life. 11 The mental health service in Norway is organized on two main levels: a specialist health service and a primary care level in the municipality.…”
Section: Introductionmentioning
confidence: 99%